2022
DOI: 10.1071/rd22139
|View full text |Cite
|
Sign up to set email alerts
|

Diurnal rhythms in testicular blood flow, testicular morphometry and reproductive hormones in Shiba goats

Abstract: Context Testicular blood flow (TBF) is crucial for testicular function. The pattern of TBF in Shiba goats indicates seasonal variations. Aims This study aimed to investigate the effect of diurnal variations on TBF, testis volume (TV), testicular echogenicity, and reproductive hormones in goats over a 24-h period. Methods In three trials that went for three consecutive days each, 12 bucks were scanned using Triplex ultrasonography to assess the TV, pixel intensity of testicular echotexture (PIX), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 52 publications
0
5
0
Order By: Relevance
“…Accordingly, differences in circadian variations of both gonadotropins might be related with the fact that differential regulation mechanisms exist for Fsh and Lh release throughout Gnrh in fish (Karigo et al, 2013). Regarding diurnal Fsh variations, changes have been also observed in male humans and rams suggesting that these circadian rhythms might be crucial for the maintenance of the physiological functions of the testis (Brambilla et al, 2009;Zhang et al, 2018;Samir et al, 2022). Effects of melatonin on testicular function and spermatogenesis in bulls have evidenced for an important role of this hormone to improve the efficiency of livestock reproduction (Li et al, 2023).…”
Section: Discussionmentioning
confidence: 99%
“…Accordingly, differences in circadian variations of both gonadotropins might be related with the fact that differential regulation mechanisms exist for Fsh and Lh release throughout Gnrh in fish (Karigo et al, 2013). Regarding diurnal Fsh variations, changes have been also observed in male humans and rams suggesting that these circadian rhythms might be crucial for the maintenance of the physiological functions of the testis (Brambilla et al, 2009;Zhang et al, 2018;Samir et al, 2022). Effects of melatonin on testicular function and spermatogenesis in bulls have evidenced for an important role of this hormone to improve the efficiency of livestock reproduction (Li et al, 2023).…”
Section: Discussionmentioning
confidence: 99%
“…Deaths and severe economic losses due to heart problems are frequently occurring in ruminant species; however, diagnostic facilities for early detection and accurate diagnosis of cardiac diseases in ruminants are still lacking [86,87]. Moreover, small ruminants such as sheep and goats are useful animal models to study the pathophysiology of ruminants and at the same time are considered efficient models for cardiovascular research [88][89][90].…”
Section: Discussion and Future Perspectivesmentioning
confidence: 99%
“…This study showed a significant elevation in CL area from Day 20 to Day 40 in pregnant buffalos compared to the non-pregnant ones with a marked elevation of plasma progesterone levels in the same group, which could indicate the importance of adequate CL area and diameter to establish the pregnancy. Concomitantly, CL blood flow increased, as evidenced by lowering Doppler indices values (8), in pregnant females compared to those in non-pregnant ones.…”
mentioning
confidence: 88%
“…This study showed that treatment of heat-stressed rams with L-carnitine (LC) exerted a significant improvement in testicular blood perfusion because of reductions of Doppler indices (resistive index: RI and pulsatility index: PI), which explain the elevation of arterial blood perfusion and decrease of the vessel resistance to blood flow (4)(5)(6). In addition, it highlighted the pivotal roles of assessing the echotexture changes of testicular parenchyma in the control and LC-treated rams by computer image analysis (7,8).…”
mentioning
confidence: 99%